PERLINDUNGAN HUKUM KONSUMEN MELALUI JAMINAN PRODUK HALAL - Misbahul Huda (Sekolah Tinggi Ilmu Hukum Awang Long, 2020)
Regarding the halalness of non-packaged food products, Law Number 8 of 1999 concerning Consumer Protection only stipulates that business actors are prohibited from producing and/or trading goods and/or services that do not comply with the provisions for halal production, as stated in the